Biological characterization of Vietnamese native wild boars in central highland (Sus scrofa) - Son, Hoang Nghia; Long, Le Thanh; Phuong Mai, Nguyen Thi (Academia Journal of Biology, 2014)
In this study, we accessed and estimated morphological characteristics of Vietnamese native wild boars (Sus scrofa) in Central Higlands. The Vietnamese native wild boars had compact body shape, compact abdorminal, long tail. The height of mature male wild boar was about 65-75 cm. The Vietnamese native wild boars had small head, long snout, small forearms and agility. The weight of mature male wild boar was about 80-100 kg. In nature, the wild boars were clustered in one group which contained 5-20 wild boars including immature wild boars, mature wild boars and aging wild boars. The mature age of The Vietnamese native wild boars was lower than other wild boars and domestic pigs that were breeding in Central Higlands. The native wild boar male were matured and able to mating at 8-10 months old. The mating season of native female wild boar was about from April to August. The mating season of wild boars in Central Highlands was at end of dry season and early rainy season. This explained for the reason why we could collect wild boars in nature at rainy season.